Positive electrode active material for secondary battery, and secondary battery
A composite positive electrode active material with specific crystal structures and ratios addresses the structural instability of conventional lithium-transition metal oxides, enhancing battery capacity and cycle performance.
Patent Information
- Application Number
- JP2021516237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-26
- Filing Date
- 2020-04-24
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2040-04-24
AI Technical Summary
Conventional lithium-transition metal composite oxides used in secondary batteries suffer from structural collapse during high-voltage charging, leading to poor cycle characteristics and reduced capacity.
A positive electrode active material composed of a first complex oxide component with O2, T2, or O6 crystal structures, and a second complex oxide component, combined in specific ratios, enhances structural stability and capacity.
The combination of these complex oxides improves cycle characteristics and maintains high capacity by preventing crystal structure collapse, with superior open circuit voltage stability.
Smart Images

Figure 0007617565000002 
Figure 0007617565000001
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material for a secondary battery and a secondary battery using the positive electrode active material.
Background Art
[0002] Conventionally, lithium transition metal composite oxides have been widely used as positive electrode active materials for secondary batteries such as lithium ion batteries. For example, Patent Document 1 discloses a lithium transition metal composite oxide having a crystal structure defined by an O2 structure and containing Li in a transition metal layer. Since such a composite oxide increases the discharge capacity by being activated under a high voltage, it is promising as a high-capacity material.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
[0004] However, conventional lithium transition metal composite oxides such as those disclosed in Patent Document 1 may have a crystal structure collapse when charging is repeated at a high voltage, and there is room for improvement particularly in cycle characteristics.
[0005] The positive electrode active material for a secondary battery according to one aspect of the present disclosure has a general formula Li α [Li x Mn y Co z Me (1-x-y-z) O2 (wherein Me is at least one selected from Ni, Fe, Ti, Bi, Nb, W, Mo, Ta, 0.5 < α < 0.85, 0.05 < x < 0.2, 0.4 < y < 0.75, 0 < z < 0.25), and a first composite oxide component having at least one crystal structure selected from an O2 structure, a T2 structure, and an O6 structure, and a general formula Li a MO b A c(wherein M is at least one selected from Ni, Co, Mn, Fe, Cu, Ti, Nb, Al, Ga, Ge, Zn, Si, Bi, Zr, Ce, Y, W, Ta, Sn, Ca, Ba, Na, A is at least one selected from F, Cl, S, 1.3 < a < 7, 2 ≤ b < 5, 0 ≤ c ≤ 0.3), and includes a second composite oxide component represented by
[0006] A secondary battery according to one aspect of the present disclosure includes a positive electrode containing the above positive electrode active material, a negative electrode, and an electrolyte.
[0007] According to the positive electrode active material which is one aspect of the present disclosure, a secondary battery with high capacity and excellent cycle characteristics can be provided.
Brief Description of the Drawings
[0008] [Figure 1] It is a cross-sectional view of a secondary battery which is an example of an embodiment.
Mode for Carrying Out the Invention
[0009] As a result of intensive studies to solve the above problems, the inventors have found that a positive electrode active material containing the above first composite oxide component and the above second composite oxide component has high capacity and excellent structural stability. By using the positive electrode active material according to the present disclosure, it is possible to increase the capacity of the battery and improve the cycle characteristics. In addition, a decrease in the open circuit voltage (OCV) after charge and discharge cycles can be suppressed.
[0010] Hereinafter, an example of an embodiment of a positive electrode active material for a secondary battery according to the present disclosure and a secondary battery using the positive electrode active material will be described in detail. Hereinafter, a cylindrical battery in which a wound electrode body 14 is housed in a bottomed cylindrical outer can 16 will be exemplified, but the outer body is not limited to a cylindrical outer can, and may be, for example, a rectangular outer can, or an outer body composed of a laminate sheet including a metal layer and a resin layer. Further, the electrode body may be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated via a separator.
[0011] FIG. 1 is a cross-sectional view of a secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the secondary battery 10 includes a wound electrode assembly 14, an electrolyte, and an outer can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the outer can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the outer can 16 is referred to as the bottom.
[0012] The electrolyte may be an aqueous electrolyte, but is preferably a nonaqueous electrolyte containing a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more of these are used as the nonaqueous solvent. The nonaqueous solvent may contain a halogen-substituted compound in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine, such as methyl fluoropropionate (FMP) or fluoroethyl acetate (FEA). For example, a lithium salt such as LiPF6 or a lithium imide salt such as LiFSI is used as the electrolyte salt. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel polymer or the like.
[0013] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all long strip-shaped bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0014] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.
[0015] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.
[0016] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0017] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.
[0018] [Positive electrode] The positive electrode 11 has a positive electrode core body and a positive electrode composite layer provided on the surface of the positive electrode core body. For the positive electrode core body, a foil of a metal stable within the potential range of the positive electrode 11 such as aluminum, a film having the metal disposed on the surface layer, etc. can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both surfaces of the positive electrode core body except for the portion to which the positive electrode lead 20 is connected. The positive electrode active material is a lithium transition metal composite oxide and contains two types of composite oxide components. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, etc. on the surface of the positive electrode core body, drying the coating film, and then compressing it to form the positive electrode composite layer on both surfaces of the positive electrode core body.
[0019] Examples of the conductive material contained in the positive electrode composite layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode composite layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. These resins may be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, polyethylene oxide (PEO), etc.
[0020] The positive electrode active material has the general formula Li α [Li x Mn y Co z Me (1-x-y-z) O2 (wherein Me is at least one selected from Ni, Fe, Ti, Bi, Nb, W, Mo, Ta, 0.5 < α < 0.85, 0.05 < x < 0.2, 0.4 < y < 0.75, 0 < z < 0.25), and a first composite oxide component represented by the general formula Li a MO b A c(In the formula, M is at least one selected from Ni, Co, Mn, Fe, Cu, Ti, Nb, Al, Ga, Bi, Zr, Ce, Y, W, Ta, Sn, Ca, Ba, Na; A is at least one selected from F, Cl, S; 1.3 < a < 7, 2 ≤ b < 5, 0 ≤ c ≤ 0.3), and contains a second composite oxide component represented by this. The positive electrode active material may contain a third composite oxide component as long as the object of the present disclosure is not impaired.)
[0021] The content of the second composite oxide component is preferably 1 to 25% by mass or less, more preferably 5 to 20% by mass, based on the total mass of the positive electrode active material. The content of the first composite oxide component is preferably 75 to 99% by mass, more preferably 80 to 95% by mass, based on the total mass of the positive electrode active material. If the abundance ratio of the first composite oxide and the second composite oxide is within this range, the structure of the positive electrode active material is likely to be stabilized, which is preferable from the viewpoints of increasing the capacity of the battery and improving the cycle characteristics.)
[0022] The positive electrode active material is, for example, a composite of the first composite oxide component and the second composite oxide component. The positive electrode active material is a particulate substance, and the composite contains a region having the first composite oxide composition and a region having the second composite oxide composition within one particle. In this case, the positive electrode active material is composed of only one type of particle. The first composite oxide composition region and the second composite oxide composition region may be uniformly present within one particle, or each region may be unevenly distributed at the center or surface of the particle. Also, a composition region in which the first composite oxide and the second composite oxide are mutually solid-solved may exist. In that case, when looking at the cross section of the active material, it is preferable that each region is 100 nm square or more.)
[0023] As a method for producing the composite as described above, for example, a method of mechanically fixing the first composite oxide and the second composite oxide using a technique such as mechanical milling, a method of generating and adhering the second composite oxide on the surface of the first composite oxide particles using a liquid phase method or a gas phase method, or a method of molding the first composite oxide and the second composite oxide into one particle by heat treatment or pressurization, etc. can be mentioned.)
[0024] The positive electrode active material may be a mixture of first composite oxide particles containing a first composite oxide component and second composite oxide particles containing a second composite oxide component. In this case, the positive electrode active material is composed of two types of particles. It is preferable that the first composite oxide particles have a large particle size and the second composite oxide particles have a small particle size, and the particle size ratio is more preferably 4:1 to 2:1. The particle size of the positive electrode active material is, for example, 5 μm or less, and preferably 3 μm or less.
[0025] The mixture may be composed of two or more types of particles. At least one of the types is a particle containing only the second composite oxide. The positive electrode active material may be, for example, a mixture of a composite of the first composite oxide component and the second composite oxide component, and the second composite oxide particles. Alternatively, it may be a mixture of the composite, the first composite oxide particles, and the second composite oxide particles. When the positive electrode active material is, for example, a mixture of the composite and the second composite oxide particles, the mass ratio of the composite to the second composite oxide particles is preferably 75:25 to 99:1.
[0026] The first composite oxide component has at least one crystal structure selected from the group consisting of an O2 structure, a T2 structure, and an O6 structure. Preferably, the main crystal structure is the O2 structure. For example, at least 50 atom % or substantially all of the crystal structure of the first composite oxide component is the O2 structure. Here, the O2 structure is a layered crystal structure in which lithium is present at the center of an oxygen octahedron and there are two types of overlapping of oxygen and transition metal per unit cell, and it belongs to the space group P63mc. Such a layered crystal structure has a lithium layer, a transition metal layer, and an oxygen layer. In the above general formula of the first composite oxide component, the lithium layer is Li α The transition metal layer is Li x Mn y Co z Me (1-x-y-z) and the oxygen layer contains O2.
[0027] When synthesizing the first composite oxide component of the O2 structure, composite oxides of the T2 structure and the O6 structure may be simultaneously synthesized as by-products. As described above, the first composite oxide component may contain composite oxides of the T2 structure and the O6 structure synthesized as by-products. Here, the T2 structure is a layered crystal structure in which lithium exists at the center of an oxygen tetrahedron, and there are two types of overlapping of oxygen and transition metals per unit cell, and belongs to the space group Cmca. The O6 structure is a layered crystal structure in which lithium exists at the center of an oxygen octahedron, and there are six types of overlapping of oxygen and transition metals per unit cell, and belongs to the space group R-3m.
[0028] In the first composite oxide component, the Li contained in the transition metal layer is more than 5 mol% and less than 25 mol%, and preferably more than 10 mol% and less than 20 mol%, based on the total molar amount of the metal elements contained in the transition metal layer. If the Li content is 25 mol% or more, a high capacity cannot be maintained. The Mn content is more than 40 mol% and less than 75 mol%, and preferably more than 50 mol% and less than 65 mol%, based on the total molar amount of the metal elements contained in the transition metal layer. The Co content is more than 0 mol% and less than 25 mol%, and preferably more than 5 mol% and less than 20 mol%, based on the total molar amount of the metal elements contained in the transition metal layer.
[0029] The metal element Me other than Li, Mn, and Co contained in the first composite oxide component is preferably at least one selected from Ni, Fe, Ti, Bi, Nb, W, Mo, and Ta. Among them, Ni and Fe are preferable. The content of Me is preferably more than 10 mol% and less than 25 mol% with respect to the total molar amount of the metal elements contained in the transition metal layer. Note that the first composite oxide component may contain metal elements other than the above as long as the object of the present disclosure is not impaired.
[0030] The first composite oxide particles containing the first composite oxide component can be synthesized by ion-exchanging Na of a sodium transition metal composite oxide containing at least Mn and Co with Li. Examples of the ion-exchange method include a method of adding a molten salt bed of a lithium salt to the sodium transition metal composite oxide and heating it. As the lithium salt, it is preferable to use at least one selected from lithium nitrate, lithium sulfate, lithium chloride, lithium carbonate, lithium hydroxide, lithium iodide, lithium bromide, and the like. Alternatively, ion-exchange may be performed by immersing the sodium transition metal composite oxide in a solution containing at least one lithium salt. Note that the ion-exchange may not proceed completely, and a certain amount of Na may remain.
[0031] As described above, the second composite oxide component has the general formula Li a MO b A c (wherein M is at least one selected from Ni, Co, Mn, Fe, Cu, Ti, Nb, Al, Ga, Ge, Zn, Si, Bi, Zr, Ce, Y, W, Ta, Sn, Ca, Ba, Na; A is at least one selected from F, Cl, S; 1.3 < a < 7, 2 ≤ b < 5, 0 ≤ c ≤ 0.3). An example of a suitable second composite oxide component is a composite oxide having a crystal structure belonging to the space group Immm, represented by the general formula Li2Ni d B 1-d O 2-c A c (wherein B is at least one selected from Ga, Bi, Y, W, Ta, Sn, Ca, Ba; 0.7 ≤ d ≤ 1), or a composite oxide having a crystal structure belonging to the space group Pbca, represented by the general formula Li2O·βCo e Ma 1-e O 1-c ·γLiFe f Ma 1-f O 2-c (wherein Ma is at least one selected from Mn, Al, Ga, Ge, Zn, Zr, Ce, Y, Sn, Si, Ti, Na; 0 ≤ β < 0.4, 0 ≤ γ < 0.6, 0 < β + γ, 0.7 ≤ e ≤ 1, 0.7 ≤ f ≤ 1 )in as represented, and having a crystal structure belonging to the space group Pbca.
[0032] Specific examples of the second composite oxide component include those having the general formula Li2NiO2, Li2Ni 0.94 Co 0.03 Al 0.03 O2, Li2Ni 0.97 Ga 0.03 O2, Li2MnO3, Li5FeO4, Li5Fe 0.8 Co 0.2 Examples of the composite oxides include those represented by the formulas O4, Li2CuO2, Li2TiO3, and Li3NbO4. The second composite oxide component may contain metal elements other than those mentioned above, provided that the object of the present disclosure is not impaired.
[0033] The second composite oxide component preferably contains Ni or Fe as the metal element M. One example of a suitable second composite oxide component is a composite oxide represented by the general formula Li2NiO2 and having a crystal structure belonging to the space group Immm. Another example of a suitable second composite oxide component is a composite oxide represented by the general formula Li5FeO4 and having a crystal structure belonging to the space group Pbca. The crystal structure of the composite oxide is analyzed by Rietveld analysis of the X-ray diffraction pattern measured with a powder X-ray diffractometer (for example, Rigaku's desktop X-ray diffractometer: Miniflex).
[0034] Furthermore, the second composite oxide component preferably contains Li2SO4. Since the second composite oxide has a high surface reactivity, it may react with the binder when preparing the positive electrode composite slurry, which may cause gelation of the positive electrode composite slurry. The inclusion of Li2SO4 reduces the reactivity of the particle surface, suppresses the reaction with the binder during composite formation, and stabilizes the process. The content of Li2SO4 is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, based on the total mass of the second composite oxide.
[0035] The second composite oxide particles containing the second composite oxide component are synthesized, for example, by mixing an oxide containing the metal element M with a lithium compound such as lithium hydroxide in a predetermined molar ratio and firing the mixture in an oxygen-free atmosphere at 650° C. to 850° C. Alternatively, a composite in which the first composite oxide component and the second composite oxide component are combined can be synthesized by heat treating the first composite oxide particles synthesized by the above ion exchange together with a lithium salt such as lithium iodide in a molten salt bed of the lithium salt.
[0036] The positive electrode active material may contain an amorphous lithium transition metal composite oxide. Upon initial charging, lithium ions are released from the lithium transition metal composite oxide, and part of the crystal structure collapses to become amorphous. The amorphous composite oxide has low reactivity, and electrolyte decomposition and gas generation are suppressed on the surface. The term "amorphous" as used herein refers to a state in which the half-width w of the diffraction line corresponding to the (101) plane of the lithium transition metal composite oxide obtained by X-ray diffraction measurement is w>0.5°.
[0037] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 21 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0038] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.
[0039] The binder contained in the negative electrode mixture layer may be, as in the case of the positive electrode 11, a fluororesin, PAN, polyimide, acrylic resin, polyolefin, or the like, but it is preferable to use styrene-butadiene rubber (SBR). The negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, or PAA or a salt thereof.
[0040] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator. EXAMPLES
[0041] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0042] <Example 1> [Synthesis of the complex (first complex oxide component A + second complex oxide component B)] Sodium carbonate (Na2CO3), lithium hydroxide monohydrate (LiOH·H2O), nickel oxide (NiO), cobalt oxide (Co2O3), and manganese oxide (Mn2O3) were mixed in a specified molar ratio and pulverized in a ball mill. The pulverized material was fired in air at 900°C to obtain sodium oxide. This sodium oxide was heated in a molten salt bed of lithium salt to exchange Na for Li, and then lithium iodide (LiI) was added to the molten salt bed and reacted to obtain a composite. The molten salt bed was obtained by mixing lithium nitrate and lithium chloride in a specified molar ratio and heating it to 280°C.
[0043] The particle diameter of the obtained composite was 3 μm. In addition, analysis by EPMA, XPS, and ICP confirmed the formation of the first composite oxide component A in the center of the composite particle and the second composite oxide component B with a thickness of 250 nm on the particle surface. The compositions of the first composite oxide component A and the second composite oxide component B in the composite were Li 0.83 (Li 0.139 Mn 0.633 Ni 0.118 Co 0.11 )O2, and Li 1.32 (M 0.553 Ni 0.158 Co 0.289 )O 2.41 The molar ratio of the composite oxides A and B in the composite was A:B=94:6.
[0044] [Preparation of positive electrode] The above composite (first composite oxide component A + second composite oxide component B) was used as the positive electrode active material. The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a mass ratio of 92:5:3, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode composite slurry. Next, this positive electrode composite slurry was applied to the surface of a positive electrode core made of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to prepare a positive electrode in which a positive electrode composite layer was formed on the positive electrode core.
[0045] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent in which fluoroethylene carbonate (FEC) and methyl fluoropropionate (FMP) were mixed in a mass ratio of 1:3.
[0046] [Preparation of secondary battery] An electrode assembly was prepared by attaching lead wires to the positive electrode and the Li metal counter electrode, and arranging the positive electrode and the counter electrode facing each other via a polyolefin separator. The electrode assembly and the nonaqueous electrolyte were enclosed in an exterior body made of an aluminum laminate film to prepare a test cell.
[0047] <Example 2> Lithium oxide (Li2O) and nickel (II) oxide (NiO) were mixed in a predetermined molar ratio and pulverized in an Ar atmosphere using a ball mill. The pulverized product was fired in an Ar atmosphere at 650°C to synthesize second composite oxide particles B (Li2NiO2). The particle size of the synthesized second composite oxide particles B was 1 μm. A positive electrode and a test cell were produced in the same manner as in Example 2, except that the second composite oxide particles B was used in addition to the composite (A+B) as the positive electrode active material. The composite (A+B) and the second composite oxide particles B were mixed in a mass ratio of 80:20. The particle size ratio of the composite (A+B) and the second composite oxide particles B was 3:1.
[0048] <Comparative Example 1> Sodium carbonate (Na2CO3), lithium hydroxide monohydrate (LiOH H2O), nickel oxide (NiO), cobalt oxide (Co2O3), and manganese oxide (Mn2O3) were mixed in a specified molar ratio and pulverized in a ball mill. The pulverized material was fired in air at 900°C to obtain sodium oxide. This sodium oxide was then heated in a molten salt bed to exchange Na for Li, producing the first composite oxide particle A (Li 0.75 (Li 0.139 Mn 0.625 Ni 0.118 Co 0.118)O2) was obtained. The particle diameter of the obtained first composite oxide particles A was 3 μm. The molten salt bed was obtained by mixing lithium nitrate and lithium chloride in a predetermined molar ratio and heating to 280° C. A positive electrode and a test cell were produced in the same manner as in Example 1, except that the second composite oxide particles B were not used as the positive electrode active material, and only the first composite oxide particles A were used.
[0049] [Evaluation of positive electrode capacity and cycle characteristics (capacity retention rate)] Each test cell of the Examples and Comparative Examples was charged and discharged under the following conditions in a temperature environment of 25° C., and the positive electrode capacity (discharge capacity at the first cycle) and the capacity retention rate after charge-discharge cycles were determined.
[0050] <Charge / discharge conditions> The battery was charged at a constant current of 0.05 C until the closed circuit voltage of the battery reached 4.7 V (based on the Li counter electrode), and then charged at a constant voltage of 4.7 V until the current value became less than 0.02 C, and then discharged at a constant current of 0.05 C until the closed circuit voltage of the battery reached 2.0 V (based on the Li counter electrode). This charge / discharge cycle was repeated 10 times, and the capacity retention rate was calculated using the following formula.
[0051] Capacity retention rate (%) = 10th cycle discharge capacity ÷ 1st cycle discharge capacity × 100 [Evaluation of ΔOCV] The difference between the OCV after the first charge in the above charge-discharge cycle and the OCV after the 10th cycle was calculated as ΔOCV.
[0052] [Table 1]
[0053] As shown in Table 1, all of the positive electrodes of the examples have higher capacity retention rates and smaller ΔOCVs than the positive electrodes of the comparative examples. In addition, all of the positive electrodes of the examples exhibit high capacities equal to or higher than those of the comparative examples. In other words, by using the positive electrode active material of the examples, the collapse of the crystal structure caused by cycling is suppressed, and both high capacity and good cycle characteristics can be achieved. [Explanation of symbols]
[0054] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket
Claims
1. General formula Li α [Li x Mn y Co z Me (1-x-y-z) ]O 2 (wherein Me is at least one selected from Ni, Fe, Ti, Bi, Nb, W, Mo, and Ta, and 0.5<α<0.85, 0.05<x<0.2, 0.4<y<0.75, and 0<z<0.25), and at least 50 atom % of the first composite oxide component has a crystal structure having an O2 structure; General formula Li a M.O. b A c (wherein M is at least one selected from Ni, Co, Mn, Fe, Cu, Ti, Nb, Al, Ga, Ge, Zn, Si, Bi, Zr, Ce, Y, W, Ta, Sn, Ca, Ba, and Na; A is at least one selected from F, Cl, and S; and 1.3<a<7, 2≦b<5, and 0≦c≦0.3), and Including, A positive electrode active material for a secondary battery, wherein the content of the second composite oxide component is 1 to 25 mass % of the total mass of the positive electrode active material.
2. The positive electrode active material according to claim 1 , which is a composite of the first composite oxide component and the second composite oxide component.
3. 2. The positive electrode active material according to claim 1, which is a mixture of first composite oxide particles containing the first composite oxide component and second composite oxide particles containing the second composite oxide component.
4. The second composite oxide component has the general formula Li 2 Ni d B 1-d O 2-c A c (wherein B is at least one selected from Ga, Bi, Y, W, Ta, Sn, Ca, and Ba; 0.7≦d≦1), and is a composite oxide having a crystal structure belonging to the space group Immm. The positive electrode active material according to any one of claims 1 to 3.
5. The second composite oxide component has the general formula Li 2 O.βCo e Ma1-eO 1-c γ LiFe f M 1-f O 2-c (wherein Ma is at least one selected from Mn, Al, Ga, Ge, Zn, Zr, Ce, Y, Sn, Si, Ti, and Na; 0≦β<0.4, 0≦γ<0.6, 0<β+γ, 0.7≦e≦1, 0.7≦f≦1), and is a composite oxide having a crystal structure belonging to the space group Pbca. The positive electrode active material according to any one of claims 1 to 3.
6. The second composite oxide component is Li 2 SO 4 The positive electrode active material according to any one of claims 1 to 3, comprising:
7. A secondary battery comprising a positive electrode containing the positive electrode active material according to any one of claims 1 to 6, a negative electrode, and an electrolyte.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery, and method of manufacturing anode active material for nonaqueous electrolyte secondary battery
JP2007242420A
Positive electrode active material and method for producing the same
JP2014130782A
Positive electrode active material for nonaqueous electrolytic secondary battery
JP2014197540A
Positive electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method of positive electrode active material for nonaqueous electrolyte secondary battery
JP2015092455A
Secondary battery
JP2015138730A